Sintilimab plus bevacizumab followed by resection in intermediate-stage hepatocellular carcinoma: a phase Ib clinical trial with biomarker analysis - Jia Fan; Shuang-Jian Qiu; Xiao-Ying Wang; Qiang Gao; Ying-Hong Shi; Yuan Ji; Cheng Huang; Hui-Chuan Sun; Xiao-Dong Zhu; Zi-Yi Wang; Ying-Hao Shen (BMJ Oncology)
Objective This phase Ib trial aimed to assess the safety and efficacy of sintilimab plus bevacizumab (sintilimab/bev), followed by resection in patients with potentially resectable intermediate-stage hepatocellular carcinoma (HCC) and explore the clinical implications of circulating tumour DNA (ctDNA) and T cell receptor (TCR) repertoire.Methods and analysis Eligible patients with intermediate-stage HCC received sintilimab/bev treatment. Patients with partial response or stable disease for at least two consecutive evaluations and technically resectable received hepatectomy. Postoperatively patients continued to receive sintilimab/bev until tumour recurrence or intolerable toxicities for up to 12 months. The primary endpoints were treatment safety and event-free survival (EFS). Plasma ctDNA measurements and TCR repertoire were analysed.Results 30 patients were enrolled. 17 (56.7%) patients received liver resection. Grade 3 treatment-related adverse events occurred in seven patients (23.3%). No grade 4/5 AE or postoperative mortality was observed. The median EFS of the 30 patients was 16.3 months (95% CI 13.4 to 19.2). The 12-month and 24-month survival rates were 93.2% and 82.0%, respectively. Of the 17 patients who received hepatectomy, the median recurrence-free survival was 14.1 months (95% CI 8.9 to 19.4). A lower ctDNA measurement and higher TCR repertoire were associated with better tumour response or patients’ survival.Conclusions The study suggested systemic therapy with sintilimab/bev was safe and effective in patients with intermediate-stage HCC, and resection in selected patients was associated with improved survival. ctDNA measurement and TCR repertoire may help identify patients who may benefit from sintilimab/bev treatment and patients with a higher risk of tumour recurrence.Trial registration number NCT04843943.